Analisis Efektivitas Penerapan Warehouse Management System (WMS) Dalam Menopang Operasi E-commerce “IND ONDERDIL” - Ricco Ivan Lee; Cicely Alvina; Gandhi Pawitan (Jurnal Media Informatika, 2025)
Digital business developments and the COVID-19 pandemic have encouraged companies such as IND ONDERDIL to transform their business into digital by utilizing e-commerce. In its operations, IND ONDERDIL uses omnichannel, including using the Warehouse Management System (WMS) feature, which plays a role in increasing sales and operational efficiency. With omnichannel, IND ONDERDIL can integrate all e-commerce which allows cross-selling to occur, as well as increasing consumer trust and loyalty. This research analyzes the effectiveness of using WMS on the timeliness of order processing and the accuracy of the quantity of goods in storage. The research uses quantitative methods with a case study approach, as well as data collection through observation and interviews. The operationalization of the effectiveness variable includes two criteria: timeliness of the process and accuracy of the quantity of goods. The research results show that the WMS used by IND ONDERDIL is effective in increasing the efficiency of order processing time and ensuring the accuracy of the quantity of goods. However, to improve performance further, companies are advised to regularly carry out stock taking to minimize inventory data errors. Apart from that, Human Resources (HR) training needs to be carried out to improve the ability to utilize technology optimally, so that processing time and accuracy improve. In conclusion, the use of WMS has a positive impact on IND ONDERDIL's operational effectiveness. The implementation of additional steps such as routine stock taking and HR training is expected to further improve the company's performance in facing digital business competition.